Intravesical Foreign Body: A Case Report - Ul Haque, Mohammed Monowar; Md Nizamuddin, - (Journal of Chittagong Medical College Teachers’ Association, 2013)
Foreign body in the urinary bladder is not very common. It may occur by self insertion or migration from neighboring organs. It represents a urologic challenge which requires prompt management and should be treated as emergencies. Most of the foreign bodies in the urinary bladder can be successfully removed endoscopically. Sometimes open surgical procedure may require in removing the foreign body. Removal of foreign body from urinary bladder may be quite challenging requiring imaginations & high level surgical skills. Here we reported a case of 29 years old mentally retarded man with an intravesical foreign body. We successfully removed the foreign body by endoscopic procedure under general anesthesia. In post operative follow up there was no voiding problem & patient was advised for psychiatric consultation. JCMCTA 2012 ; 23 (2): 47-49